Pemanfaatan Indeksasi Mendeley Sebagai Media Pengenalan Jurnal STT Yuppentek - Handayani, Indri; Febriyanto, Erick; Yudanto, Teguh Arya (Technomedia Journal, 2019)
Scientific works or journals at STT Yuppentek are currently less globally known and indexation is an important element to increase the popularity of scientific papers or journals. Mendeley is a software that is devoted to integrating citation & reference managers into a social network, where researchers in various parts of the world can collaborate and share research data. Mendeley can be accessed through desktop, web and mobile applications by providing full-text search for all papers in the database and sharing documents on the database with other users and synchronizing reference libraries with data stored on Mendeley's web server. However, there are several problems faced in the research at STT Yuppentek, namely the lack of quality and authenticity of scientific works or journals, and the popularity of scientific works or STT Yuppentek journals in global circles. This research was carried out using data collection methods, problem analysis and needs analysis because the method was in accordance with this study to identify the problem at hand. The results of this study are applying the management application of quotes and references from the STT Yuppentek journal and increasing the popularity of scientific papers or STT Yuppentek journals globally. Keywords: Indexation, Yuppentek STT Journal, Mendeley.